Eco-friendly healing agents for recycled concrete - Garcia-Gonzalez, Julia (2018)
Abstract An innovative option to extend the service life of construction and building materials is the use of bio-healing agents. This study was focused on assessing the protection and consolidation effect of eco-friendly healing agents by analysing the water absorption of recycled concrete. A recycled concrete with 50% replacement of natural coarse aggregate by construction and demolition waste (CDW) aggregate and a similar recycled concrete in which, additionally, the Portland cement was replaced by recycled cement (with 25% ceramic waste) were biotreated by healing agents. These agents were obtained by using waste biomass of two different mixed microbial cultures from polyhydroxyalkanoates production processes. Results have shown that biotreatments decreased the water absorption significantly, more evident in concrete samples with both recycled cement and aggregates than on the other type of concrete. Resumen Una innovadora posibilidad planteada para prolongar la vida útil de los materiales de construcción y edificación es el uso de agentes bioreparadores. Este estudio se centró en la evaluación del efecto protector y consolidante de agentes reparadores y respetuosos con el medio ambiente mediante el análisis de la absorción de agua del hormigón reciclado. Un hormigón reciclado con sustitución del 50% de los áridos gruesos naturales por residuos de construcción y demolición (RCD) y un hormigón reciclado similar en el cual, además, se sustituyó el cemento convencional Portland por cemento reciclado (con 25% de residuo cerámico) fueron biotratados con agentes reparadores. Estos agentes se obtuvieron en el proceso de producción de polihidroxialcanoatos utilizando biomasa residual de dos cultivos microbianos mixtos diferentes. Los resultados mostraron que los biotratamientos disminuyen significativamente la absorción de agua del hormigón, siendo más eficaces en las muestras de hormigón que combinan cemento y árido reciclado que en el otro tipo de hormigón.